2004
DOI: 10.1590/s1516-35982004000500013
|View full text |Cite
|
Sign up to set email alerts
|

Exigências de mantença e de ganho de proteína e de energia em codornas japonesas (Coturnix coturnix japonica) na fase de 1 a 12 dias de idade

Abstract: RESUMO -Este experimento foi conduzido com o objetivo de estimar as exigências em proteína e energia para mantença e ganho em 384 fêmeas de codornas japonesas de 1 a 12 dias de idade. Utilizou-se um delineamento inteiramente ao acaso com quatro tratamentos, composto por seis repetições de dez aves. Os tratamentos foram: T 1 = dieta basal (DB) com 28% de proteína bruta (PB) e 2.900 kcal de energia metabolizável aparente corrigida pelo balanço de nitrogênio (EMAn) fornecida à vontade; T 2 = 80%; T 3 = 60%; e T 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0
20

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 15 publications
4
9
0
20
Order By: Relevance
“…Therefore, weight and egg mass decreased with food restriction increase due to lower protein intake. There was decrease in consumption and energy and protein retentions and heat production (Table 3) as basal diet supply was reduced in agreement with previous studies on chickens (Albino et al, 1994), young quails (Silva et al, 2004a) and growing quails (Silva et al, 2004b). Decreased consumption, decreased retention and heat production of quails was greater at the more severe restriction levels of consumption, indicating that the nutrients intake was not sufficient to meet the requirements for maintenance and egg production.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, weight and egg mass decreased with food restriction increase due to lower protein intake. There was decrease in consumption and energy and protein retentions and heat production (Table 3) as basal diet supply was reduced in agreement with previous studies on chickens (Albino et al, 1994), young quails (Silva et al, 2004a) and growing quails (Silva et al, 2004b). Decreased consumption, decreased retention and heat production of quails was greater at the more severe restriction levels of consumption, indicating that the nutrients intake was not sufficient to meet the requirements for maintenance and egg production.…”
Section: Resultssupporting
confidence: 88%
“…During the Japanese quails' performance (Table 2), there was a decrease in features as the supply of basal diet was reduced, according to results observed in pullets (Albino et al, 1994), young quails (Silva et al, 2004a) and quails at growth (Silva et al, 2004b).…”
Section: Resultsmentioning
confidence: 63%
“…Silva & Costa (2009) showed that European quails had higher rate of daily gain and higher weight at maturity than the Japanese quails. These differences were confirmed by comparing the results of weight gain of Japanese quails from 2.76 g/hen/day of 1-12 days of age (Silva et al, 2004a) with the weight gain of European quails 3.27 g/hen/day of 1-14 days of age (Rezende et al, 2004).…”
Section: Resultsmentioning
confidence: 89%
“…A diferença entre os genótipos pode ser atribuída às divergências genéticas, onde codornas europeias apresentam maior taxa de deposição para proteína (JORDÃO FILHO et al, 2012) exigem mais energia para mantença e são mais eficientes no uso da energia (Jordão Filho et al, 2011) e proteí-na para ganho que codornas japonesas (JORDÃO FILHO et al, 2012). De acordo com Silva et al (2004a), codornas japonesas aumentam o peso vivo em cerca de sete vezes de um a 14 dias de idade. No entanto, Silva et al (2004b) em outro trabalho, não encontraram a mesma evolução do peso vivo das codornas na fase de crescimento (15 a 32 dias).…”
Section: Resultsunclassified